ANALYSIS OF ASIR VARIATION EFFECT TO SNR ON UNENHANCED ABDOMINAL CT SCAN IN UROLITHIASIS - Pratama Putra, Rizki Aditiya; Rahardjo, Paulus; Pramono, Pramono (Journal of Vocational Health Studies, 2020)
Background: Adaptive Statistical Iterative Reconstruction (ASIR) reconstruction in unenhanced abdominal CT scan reduce the radiation dose from 11.6 mSv to 2.07 mSv. However, the decrease in dose is accompanied by a decrease in image quality. Signal to Noise Ratio (SNR) is one of image quality parameters. Purpose: This study aims to determine the effect of the ASIR method on the optimal Signal to Noise Ratio (SNR) value in unenhanced abdominal CT of urolithiasis in clinical data. Method: 27 samples collected and the SNR was measured on the ASIR reconstruction results at the level of 40%, 50%, 60% by placing the ROI in organ structures with different densities. Result: The results of this study indicate that the ASIR method has a significant effect on the SNR value. Based on the linear regression test, the value was 0.005 ( p< 0.05) and only had an effect of 9.5% on SNR. Conclusion: It can be concluded that the ASIR method affects the optimal SNR value for unenhanced abdominal CT on urolithiasis. The ASIR 60% level was recommended.